Mucosal adjuvants - Freytag, L.C.; Clements, J.D. (Vaccine, 2005)
Induction of immune responses following oral immunization is frequently dependent upon the co-administration of appropriate adjuvants that can initiate and support the transition from innate to adaptive immunity. The three bacterial products with the greatest potential to function as mucosal adjuvants are the ADP-ribosylating enterotoxins (cholera toxin and the heat-labile enterotoxin of Escherichia coli), synthetic oligodeoxynucleotides containing unmethylated CpG dinucleotides (CpG ODN), and monophosphoryl lipid A (MPL). The mechanism of adjuvanticity of the ADP-ribosylating enterotoxins is the subject of considerable debate. Our own view is that adjuvanticity is an outcome and not an event. It is likely that these molecules exert their adjuvant function by interacting with a variety of cell types, including epithelial cells, dendritic cells, macrophages, and possibly B- and T-lymphocytes. The adjuvant activities of CpG and MPL are due to several different effects they have on innate and adaptive immune responses and both MPL and CpG act through MyD88-dependent and -independent pathways. This presentation will summarize the probable mechanisms of action of these diverse mucosal adjuvants and discuss potential synergy between these molecules for use in conjunction with plant-derived vaccines.